2004
DOI: 10.1038/sj.bjc.6602030
|View full text |Cite
|
Sign up to set email alerts
|

Coordinate hypermethylation at specific genes in prostate carcinoma precedes LINE-1 hypomethylation

Abstract: In prostate carcinoma (PCa) increased DNA methylation ('hypermethylation') occurs at specific genes such as GSTP1. Nevertheless, overall methylation can be decreased ('hypomethylation') because methylation of repetitive sequences like LINE-1 retrotransposons is diminished. We analysed DNA from 113 PCa and 36 noncancerous prostate tissues for LINE-1 hypomethylation by a sensitive Southern technique and for hypermethylation at eight loci by methylation-specific PCR. Hypermethylation frequencies for GSTP1, RARB2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
139
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(152 citation statements)
references
References 26 publications
10
139
3
Order By: Relevance
“…24 Moreover, it has been suggested that a high de-repression, via hypomethylation, of LINE-1 promoter could induce a general dysregulation that involves chromosomal instability, reactivation of repeated sequences, and oncogenes. 24,22 Our results are consistent with these suggestions, as the association between LINE-1 hypomethylation and mortality from prostate cancer was limited to men with an aggressive tumor (Gleason score 8C). On the other hand, there was no association between LINE-1 methylation and Gleason score.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…24 Moreover, it has been suggested that a high de-repression, via hypomethylation, of LINE-1 promoter could induce a general dysregulation that involves chromosomal instability, reactivation of repeated sequences, and oncogenes. 24,22 Our results are consistent with these suggestions, as the association between LINE-1 hypomethylation and mortality from prostate cancer was limited to men with an aggressive tumor (Gleason score 8C). On the other hand, there was no association between LINE-1 methylation and Gleason score.…”
Section: Discussionsupporting
confidence: 81%
“…On the other hand, there was no association between LINE-1 methylation and Gleason score. Although this latter finding is not completely inconsistent with previous studies (a clear association between LINE-1 hypomethylation and Gleason score has been found only in one out of 3 previous studies 22,23,26 ), if global methylation was a late event in prostate cancerogenesis, we would have expected higher hypomethylation among patients with a Gleason score of at least 8. It could be speculated that global methylation is more related to the metastatic potential of aggressive prostate cancers than to the Gleason score, and it is of interest that previous studies strongly indicate a decreased global methylation in the prostate cancer tissue among prostate cancer patients with systemic metastases.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…DNA methylation (and heterochromatin in general) has been reported to suppress homologous recombination (Pàldi et al, 1995;Maloisel and Rossignol, 1998;Schnable et al, 1998;Fu et al, 2002;Yao et al, 2002;Yamada et al, 2004;Myers et al, 2005) as well as transposition (Yoder et al, 1997;Walsh et al, 1998;Hirochika et al, 2000;Robertson, 2001;Bird, 2002;Kato et al, 2003). Accordingly, reports of deletions caused by homologous recombination between LINE-1 elements are rare (Segal et al, 1999) except in cancers (Florl and Schulz, 2003) where LINE-1 elements are frequently hypomethylated (Santourlidis et al, 1999;Takai et al, 2000;Ehrlich, 2002;Carnell and Goodman, 2003;Florl et al, 2004;Roman-Gomez et al, 2005). LINE-1 transposition has also been reported to be elevated in cancers (Schulz, 2006).…”
Section: Non-random Repeat Distributions Via Natural Selectionmentioning
confidence: 99%
“…28 Esteller et al showed that 18% of sporadic colorectal carcinoma and adenoma harbour a methylated APC promoter, that in 95% of cases, methylation affects the wild-type allele and that neoplasia with methylation fail to express the APC transcript. 26 Studies in lung, prostate and breast cancer also demonstrated frequent APC methylation, [29][30][31] whereas there is no data concerning APC methylation frequencies in sarcoma. Our analysis of 20 myxoid/round-cell LPS samples revealed methylation in 45% of cases and showed that most methylated tumours displayed a lower APC transcript level than nonmethylated tumours.…”
Section: Discussionmentioning
confidence: 99%